Progress in the prevention of mother to child transmission of HIV in three regions of Tanzania: a retrospective analysis. - Ann M Buchanan (Public Library of Science (PLoS), 2014)
Background Mother to child transmission (MTCT) of HIV-1 remains an important problem in sub-Saharan Africa where most new pediatric HIV-1 infections occur. Early infant diagnosis of HIV-1 using dried blood spot (DBS) PCR among exposed infants provides an opportunity to assess current MTCT rates. Methods We conducted a retrospective data analysis on mother-infant pairs from all PMTCT programs in three regions of northern Tanzania to determine MTCT rates from 2008-2010. Records of 3,016 mother-infant pairs were assessed to determine early transmission among HIV-exposed infants in the first 75 days of life. Results Of 2,266 evaluable infants in our cohort, 143 had a positive DBS PCR result at ≤ 75 days of life, for an overall transmission rate of 6.3%. Transmission decreased substantially over the period of study as more effective regimens became available. Transmission rates were tightly correlated to maternal regimen: 14.9% (9.5, 20.3) of infants became infected when women received no therapy; 8.8% (6.9, 10.7) and 3.6% (2.4, 4.8) became infected when women received single-dose nevirapine (sdNVP) or combination prophylaxis, respectively; the lowest MTCT rates occurred when women were on HAART, with 2.1% transmission (0.3, 3.9). Treatment regimens changed dramatically over the study period, with an increase in combination prophylaxis and a decrease in the use of sdNVP. Uptake of DBS PCR more than tripled over the period of study for the three regions surveyed. Conclusions Our study demonstrates significant reductions in MTCT of HIV-1 in three regions of Tanzania coincident with increased use of more effective PMTCT interventions. The changes we demonstrate for the period of 2008-2010 occurred prior to major changes in WHO PMTCT guidelines.